Genetic association study of coeliac disease in the Irish population - Brophy, Karen (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2007)
The aim of the present study was to investigate the genetic contribution of genes or regions other than the HLA to coeliac disease (CD) susceptibility in the Irish population. Genes selected for analysis in this study were chosen based on evidence from previous studies suggesting a genetic or functional association between the gene of interest and autoimmune disease. Genomic regions were also selected for analysis and subsequently screened for candidate genes, based on evidence from previous genome scans which identified regions linked to CD. All genes selected for analysis in this study have potential immunological functions which may contribute to the pathogenesis of coeliac disease. These include CTLA4, ICOS and CD28 on chromosome 2q33, IL10RA, CD3D, CD3E, CD3G, THY1 and IL18 on chromosome 11q23, and TNFSF14 (LIGHT) on chromosome 19p13.3, and a number of MHC class III genes located between the BAT1 and DDAH genes. 394 coeliac disease patients and 354 ethnically matched healthy controls were genotyped at a total of 61 single nucleotide polymorphisms (SNPs) over 20 genes using RFLP-PCR, Taqman or Amplifluor technologies. SNPs were selected based on either their ability to tag haplotypes (haplotype tagging SNPs), their ability to change the amino acid sequences of a gene (non-synonymous SNPs) or their potential to alter gene expression (transcription factor binding site altering SNPs).
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin